TODAY'S PROBLEMS AND WAYS OF SOLVING THE PROBLEMS OF GREEN ECONOMY - Todjiboeva Nargiza Jumaboevna (American Journals, 2024)
While the concept of a green economy holds significant promise for addressing environmental and social challenges, it also faces several problems and obstacles in today's world. Addressing these problems requires a concerted effort from governments, businesses, and civil society. While challenges exist, the transition to a green economy remains crucial for mitigating environmental crises and ensuring long-term prosperity. The article discusses about the problems and also developing and implementing effective policies, fostering innovation, ensuring equitable transitions, and educating the public about the importance of sustainability.
Keywords: Green technologies, sustainable practices, resource-efficient solutions, innovation renewable energy, clean transportation, reduction targets, policies, programs.